Is epidemiology ready for Big Software?. Issue 1 (30th January 2019) - Kerr, Cliff C
Abstract: Large-scale, open-source software projects like EMOD offer a new approach to epidemiological modeling. Built by a team of professional software developers, EMOD offers significant advantages over 'single-use' models designed by individual research teams, including comprehensive documentation, automated testing and extensive support. In addition, as an individual-based model, it allows much greater complexity and flexibility than the compartmental models that are most commonly used in epidemiology. Adopting modern software development practices, as embodied by EMOD, is essential for ensuring that the best models are available to the greatest number of people. Abstract : EMOD is unique in being a professionally designed, open-source software project as well as being an individual-based model; both aspects give it many advantages over the types of models most commonly used in epidemiology.